A Review: Green Life And Behavior Change for Net Zero by Non Governmental Organizations - Wisnu Prayogo; Rachmat Mulyana; Janter Pangaduan Simanjuntak; I Wayan Koko Suryawan; Laili Fitria; Edo Barlian; Putri Lynna A. Luthan; Dion Awfa; Ahmad Daudsyah Imami; Rifka Noor Azizah; Ani Purwanti; Sitepu Amrina Rosyada; Vemi Ridantam; Zhilli Izzadati Khairuni (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2023)
Global warming and environmental issues are being caused by the overuse of fossil fuels and increased industrialization around the world, which has resulted in the production of greenhouse gases. As a result, it's crucial to reach net-zero carbon emissions. By balancing the total quantity of carbon dioxide or other greenhouse gas emissions over a specific period and taking actions that are ecologically responsible, net zero carbon emissions can be accomplished. For environmental sustainability to be successful, it must be able to influence people's attitudes and behavior toward the environment. To understand NGOs' obligations in supporting net-zero carbon emissions, this paper presents a methodical debate utilizing NGOs as case studies. The method is employed in this work by reviewing the body of primary and secondary research on the study issue. This essay initially lists different environmental NGOs organizations before categorizing and outlining some of the significant GHGs reduction initiatives made by these organizations. This essay also addresses key issues that must be addressed upon to achieve the best outcomes. This report gives a broad overview of the synergizing domains that NGOs around the globe work in to assist improvement environmental security.